Changes in the integument across the lifespan - Keryln Carville (Wound Practice and Research, 2024)
The integumentary system is the largest and most visible body organ and is composed of the skin, hair, nails, sebaceous glands, eccrine and apocrine sweat glands. Integumentary assessment, prevention of its injury and management of the injury or other defect, should it occur, is a paramount goal for all clinicians across all health domains. Furthermore, it is a fundamental requirement for ensuring quality care outcomes. However, in order to conduct a comprehensive and informative assessment the clinician needs to recognise and consider the normal skin characteristics that present across the lifespan in order to identify any pathological  presentations. The major lifespan periods that influence the integumentary system changes are: neonatal, childhood, adolescence, pregnancy, adulthood and elderly time periods.